2002
DOI: 10.1046/j.1523-1755.2002.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-induced apoptosis in glomerular mesangial cells

Abstract: The observations indicate that ADO induces mesangial cell apoptosis via stimulation of the A3 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…More recent studies using various cell types that implicate increased adenosine toxicity via increased SAH levels have employed comparable adenosine concentrations as used by us [24,[26][27][28][29]42]. The mechanism of action of adenosine appears to be via its ability to act as a substrate for as well as an inhibitor of SAH hydrolase thereby elevating intracellular SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies using various cell types that implicate increased adenosine toxicity via increased SAH levels have employed comparable adenosine concentrations as used by us [24,[26][27][28][29]42]. The mechanism of action of adenosine appears to be via its ability to act as a substrate for as well as an inhibitor of SAH hydrolase thereby elevating intracellular SAH.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there have been reports of increased intracellular SAH levels inducing apoptosis in many different cell types [23][24][25][26][27][28][29]. Therefore, we put forth the hypothesis that increased intracellular SAH generation may be responsible for hepatocyte apoptosis seen after ethanol administration.…”
Section: Introductionmentioning
confidence: 95%
“…A 2 receptors have been identified on human glomerular mesangial cells [350]. Adenosine activates mesangial cell proliferation [235], but can also induce apoptosis of mesangial cells [437]. High concentrations of glucose increase extracellular levels of ATP in mesangial cells, which in turn activates ERK1/2.…”
Section: Mesangial Cellsmentioning
confidence: 99%
“…In these experiments, cells were treated with 10 μM of different adenine nucleotides, and the number of cells that migrated into the leasioned area of 1 mm 2 in size was counted 24 h later [57]. Increases in migration were induced by cAMP, adenosine, AMP, and ATP suggesting purinergic receptors activation; however, P1 receptors may promote contrary functions in this context, as adenosine can induce apoptosis in glomerular mesangial cells causing glomerular injury [58]. Babelova et al showed that the secretion of the pro-inflammatory master cytokine interleukin (IL)-1β during inflammatory renal injury interacts with purinergic P2X4/P2X7 receptors [59].…”
Section: Bladder Dysfunction and Glomerular Injurymentioning
confidence: 99%